European Academy of Neurology/Peripheral Nerve Society Guideline on diagnosis and treatment of Guillain–Barré syndrome - Doorn, Pieter A.; Van den Bergh, Peter Y. K.; Hadden, Robert D. M.; Avau, Bert; Vankrunkelsven, Patrik; Attarian, Shahram; Blomkwist‐Markens, Patricia H.; Cornblath, David R.; Goedee, H. Stephan; Harbo, Thomas; Jacobs, Bart C.; Kusunoki, Susumu; et al. (European journal of neurology, 2023)
Guillain–Barré syndrome (GBS) is an acute polyradiculoneuropathy. Symptoms may vary greatly in presentation and severity. Besides weakness and sensory disturbances, patients may have cranial nerve involvement, respiratory insufficiency, autonomic dysfunction and pain. To develop an evidence‐based guideline for the diagnosis and treatment of GBS, using Grading of Recommendations, Assessment, Development and Evaluation (GRADE) methodology a Task Force (TF) of the European Academy of Neurology (EAN) and the Peripheral Nerve Society (PNS) constructed 14 Population/Intervention/Comparison/Outcome questions (PICOs) covering diagnosis, treatment and prognosis of GBS, which guided the literature search. Data were extracted and summarised in GRADE Summaries of Findings (for treatment PICOs) or Evidence Tables (for diagnostic and prognostic PICOs). Statements were prepared according to GRADE Evidence‐to‐Decision (EtD) frameworks. For the six intervention PICOs, evidence‐based recommendations are made. For other PICOs, good practice points (GPPs) are formulated. For diagnosis, the principal GPPs are: GBS is more likely if there is a history of recent diarrhoea or respiratory infection; CSF examination is valuable, particularly when the diagnosis is less certain; electrodiagnostic testing is advised to support the diagnosis; testing for anti‐ganglioside antibodies is of limited clinical value in most patients with typical motor‐sensory GBS, but anti‐GQ1b antibody testing should be considered when Miller Fisher syndrome (MFS) is suspected; nodal–paranodal antibodies should be tested when autoimmune nodopathy is suspected; MRI or ultrasound imaging should be considered in atypical cases; and changing the diagnosis to acute‐onset chronic inflammatory demyelinating polyradiculoneuropathy (A‐CIDP) should be considered if progression continues after 8 weeks from onset, which occurs in around 5% of patients initially diagnosed with GBS. For treatment, the TF recommends intravenous immunoglobulin (IVIg) 0.4 g/kg for 5 days, in patients within 2 weeks (GPP also within 2–4 weeks) after onset of weakness if unable to walk unaided, or a course of plasma exchange (PE) 12–15 L in four to five exchanges over 1–2 weeks, in patients within 4 weeks after onset of weakness if unable to walk unaided. The TF recommends against a second IVIg course in GBS patients with a poor prognosis; recommends against using oral corticosteroids, and weakly recommends against using IV corticosteroids; does not recommend PE followed immediately by IVIg; weakly recommends gabapentinoids, tricyclic antidepressants or carbamazepine for treatment of pain; does not recommend a specific treatment for fatigue. To estimate the prognosis of individual patients, the TF advises using the modified Erasmus GBS outcome score (mEGOS) to assess outcome, and the modified Erasmus GBS Respiratory Insufficiency Score (mEGRIS) to assess the risk of requiring artificial ventilation. Based on the PICOs, available literature and additional discussions, we provide flow charts to assist making clinical decisions on diagnosis, treatment and the need for intensive care unit admission.